Metrological advancements in cognitive measurement: A worked example with the NeuroMET memory metric providing more reliability and efficiency. (February 2023) - Melin, J.; Cano, S.J.; Flöel, A.; Göschel, L.; Pendrill, L.R.
Abstract: Better metrics of cognition can be formed by carefully combining selected items from legacy short-term memory tests so as to enhance coherence in item design while not jeopardizing validity. In this paper, we report on how Rasch Measurement Theory and Construct specification equations (CSE) have been brought together when composing the NeuroMET Memory Metric (NMM). The NMM is guided by: i) entropy-based equivalence criteria; ii) a comprehensive understanding of the construct purported to be measured; and iii) how a collection of items works together. CSEs play a major role in ensuring the metrological legitimacy of the NMM in a way analogous to certified reference materials in more established areas of metrology. The resulting NMM for short-term memory recall has up to a five-fold reduction in measurement uncertainties for memory ability compared with an individual legacy test, and the entropy-based CSEs should enable more efficient and valid assessment.